2015
DOI: 10.1126/scisignal.aaa5903
|View full text |Cite
|
Sign up to set email alerts
|

The mTORC1/4E-BP pathway coordinates hemoglobin production with L -leucine availability

Abstract: In multicellular organisms, the mechanisms by which diverse cell types acquire distinct amino acids and how cellular function adapts to their availability are fundamental questions in biology. Here, we found that increased neutral essential amino acid (NEAA) uptake was a critical component of erythropoiesis. As red blood cells matured, expression of the amino acid transporter gene Lat3 increased, which increased NEAA import. Inadequate NEAA uptake by pharmacologic inhibition or RNAi-mediated knockdown of LAT3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 106 publications
4
64
0
1
Order By: Relevance
“…It has been previously shown that the mTOR pathway is involved in regulating the growth and proliferation of red blood cells, both in vitro and in vivo . The mTOR complex 1 pathway has been identified as a critical regulator of red blood cell growth and proliferation . The use of mTOR inhibitors in normal and β‐thalassemia patients has increased; in vitro, the expression of fetal hemoglobin is increased to higher levels than those obtained with hydroxyurea .…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that the mTOR pathway is involved in regulating the growth and proliferation of red blood cells, both in vitro and in vivo . The mTOR complex 1 pathway has been identified as a critical regulator of red blood cell growth and proliferation . The use of mTOR inhibitors in normal and β‐thalassemia patients has increased; in vitro, the expression of fetal hemoglobin is increased to higher levels than those obtained with hydroxyurea .…”
Section: Discussionmentioning
confidence: 99%
“…To determine how Fam210b is developmentally regulated, we performed RNA sequencing (RNAseq) on transcripts from murine fetal liver erythroid cells (34) that were sorted into fractions corresponding to their stage of maturation (R1-R5) (15, [37][38][39]. Fam210b expression was up-regulated during maturation from R2 to R3, which corresponds to the developmental shift from TER119 Ϫ to TER119 ϩ expression.…”
Section: Fam210b Is An Immediate Early Target Of Epo During Terminal mentioning
confidence: 99%
“…mTORC1 regulates hematopoietic stem cell renewal and differentiation (108) and hematopoiesis through raptor (109). mTORC1 also regulates erythrocyte growth and proliferation (110) and hemoglobin synthesis (111). Cellular iron homeostasis is modulated by the iron-responsive element/iron-regulatory protein (IRE/IRP) regulatory network (112) and hepcidin (113).…”
Section: Role Of the Master Growth Regulator Mtorc1 In Child Growthmentioning
confidence: 99%